Persistence of cattle ranching in the Brazilian Amazon: A spatial analysis of the rationale for beef production - Bowman, Maria S.; Soares-Filho, Britaldo S.; Merry, Frank D.; Nepstad, Daniel C.; Rodrigues, Hermann; Almeida, Oriana T. (Land use policy, 2012)
► 9–13% of land in the Amazon is vulnerable to speculation. ► Land speculation contributes to the persistence of extensive ranching in Brazil. ► Enforcing forest law and land tenure reform are crucial for ranching intensification. Fed by demand for beef within Brazil and in global markets, the Brazilian herd grew from 147 million head of cattle in 1990 to ≈200 million in 2007. Eighty-three percent of this expansion occurred in the Amazon and this trend is expected to continue as the industry bounces back from a recent agricultural downturn. Intensification of the cattle industry has been suggested as one way to reduce pressure on forest margins and spare land for soybean or sugarcane production, and is the cornerstone of Brazil's plan for mitigation of greenhouse gas emissions. To this end, federal credit programs and research and development activities in Brazil are aligning to support intensification goals, but there is no guarantee that this push for intensification will decrease the demand for land at the forest margin and as result curb CO 2 emissions from deforestation. In this paper we use a spatially explicit rent model which incorporates the local effects of biophysical characteristics, infrastructure, land prices, and distance to markets and slaughterhouses to calculate 30-year Net Present Values (NPVs) of extensive cattle ranching across the Brazilian Amazon. We use the model to ask where extensive ranching is profitable and how land acquisition affects profitability. We estimate that between 17% and 80% of land in the Amazon would have moderate to high NPVs when ranched extensively if it were settled, i.e. if the rancher does not buy the land but acquires it through land grabbing. In addition, we estimate that between 9% and 13% of land in the Amazon is vulnerable to speculation (i.e. areas with positive NPVs only if land is settled and not purchased), which suggests that land speculation is an important driver of extensive ranching profitability, and may continue to be in the future. These results suggest that pro-intensification policies such as credit provision for improved pasture management and investment in more intensive production systems must be accompanied by implementation and enforcement of policies that alter the incentives to clear forest for pasture, discourage land speculation, and increase accountability for land management practices if intensification of the cattle sector is to deter new deforestation and displace production from low-yield, extensive cattle production systems in frontier regions of the Brazilian Amazon.